HUBUNGAN ANTARA BERAT BADAN LAHIR RENDAH DENGAN KEJADIAN ASFIKSIA DI RUMAH SAKIT UMUM DAERAH LASINRANG PINRANG - ., Fitria (Jurnal Martenity and Neonatal, 2018)
Background : LBW and Asphyxia is a problem in newborns. There was an increase of about 8-12% annually. Based on medical records in hospitals Lasinrang Pinrang in the period January to July 2015 there were 1013 babies born and most experienced LBW and Asiksia Neonatorum.Research : This study aims to determine the relationship with the incidence of LBW Infants Asphyxia Neonatorum in hospitals Lasinrang Pinrang.Method : This study used a cross-sectional study in which the measurement or observation independ- ent and the dependent variable data only once during the study, so there is no follow-up. The population is all babies born in the period from January to July 2015 in hospitals Lasinrang Pinrang the number 1013 with the simple random sampling technique. so the number of samples is 91 babies. Analisia data used is the Chi squre by using SPSS.Results : Research shows that there are 41 no LBW and not asphyxia (45.05%), whereas low birth weight infants and infant asphyxia 6 (6.59%) and low birth weight infants and infant asphyxia by 8 (8.79%, while the LBW infants and asphyxia 36 infants (39.56%). Based on the results of statistical Chi square test p-value of 0.000 was obtained, or the value of p <Î± 0,05 so of this study are significant correlation with the incidence of low birth weight babies in hospital neonatal asphyxia Lasinrang Pinrang.Conclusion : The conclusion of the study There are significant correlation with the incidence of low birth weight babies in hospital neonatal asphyxia Lasinrang Pinrang and advice The need for a more in-depth study regarding the handling of LBW so as to reduce the incidence of asphyxia in newborns in order not to impact on brain development in the future.